Identification of Adverse Drug Reactions in Congestive Heart Failure Patients in a Tertiary Care Hospital, West Nusa Tenggara, Indonesia - Lupitaningrum, Dita Marina; Ramdaniah, Putri; Yuliana, Depi (UI Scholars Hub, 2021)
Congestive Heart Failure (CHF) is a progressive health problem with high mortality and morbidity and has the potential to develop adverse drug reactions (ADRs). This study was conducted to determine the prevalence of potential ADRs, the types of drugs that cause ADRs, the types of ADRs, and the risk factors that affect the ADRs in CHF patients. Data were collected using medical record of hospitalized patient at the West Nusa Tenggara (NTB) Provincial Hospital, Indonesia, in 2017 to 2019. The assessment of the causality and severity of ADRs used the Naranjo algorithm and the Hartwig and Siegel scale. This study used 325 CHF patients’ data. Of 325 CHF patients, 223 patients (69%) were recorded as having ADRs with 446 total cases of ADRs, consisted of 4 (0.9%) highly probable, 187 (41.9%) probable, and 255 (57.2%) possible. The drugs that cause ADRs with a highly probable status are bisoprolol and ramipril. The most ADRs categories were level 1 (76.0%), followed by level 2 (17.3%), level 3 (6.5%), and level 4A (0.2%). The most affected organ systems were the muscles, joints, and nervous system (n=136, 37.7%), followed by renal, and gastrointestinal system. No association between ADRs with several risk factors, such as gender, age, and comorbidities. The prevalence of ADRs in CHF patients in this study was 69%, with the highly probable category in causing ADRs were bisoprolol and ramipril. ADRs that mostly occurred were in the mild category. ADRs monitoring in CHF patients is especially important to achieve optimal therapeutic results.